Pengaruh Kemampuan Penalaran Terhadap Kemampuan Pemecahan Masalah Matematis Pada Siswa SMP - NurJannah, Salsabilla Agatha (Papanda, 2025)
This study aims to identify the effect of reasoning ability on the problem solving ability of class VIII students. The method used was ex post facto research with a quantitative approach. The study population included all students of grade VIII of SMPN 2 Tempuran. Sampling using simple random sampling technique so that a sample of 80 students was obtained. The data collection technique of this research is a written test of two packages of questions with the number of questions of reasoning ability 5 questions and problem solving ability 4 questions. The research was conducted in one meeting, where the research instruments were distributed to all sample class students. Data analysis using descriptive statistical data analysis techniques and inferential statistical data analysis showed that reasoning ability has an influence of 53% on students' problem solving ability. And there is a significant influence between reasoning ability on mathematical problem solving ability of junior high school students.